Fundamental of Entrepreneurship ENT300: Unique Sarawak Layer Cake / Eleopatra Marten ... [et al.] - Marten, Eleopatra; Maslie, Riney; Abu Seman, Siti Nurhikmah; Bakeri, Zarina (2007)
Our company name is Unique Sarawak Layer Cake. The business has been decided on the form of partnership, which consists of four members. Each partner contributes certain amount of capital as agreed in our agreement. Our main business activity is manufacturing layer cake and selling our product to the customer. We have decide that our business will operate at Parcel No 6, Lorong : 4 Desa llmu, Jalan Dato’ Mohd. Musa, 94300 Kota Samarahan, Sarawak. This will fully operate 1st January 2008. All partners are encourage and entitled to participate in all the business " in management. We have agreed that Eleopatra Marten General Manager, as well as the Administrative Manager, Zarina binti Bakeri will act as our Marketing Manager, while Riney binti Maslie will hold the post of Operational Manager and Siti Nurhikmah binti Abu Seman had been appointed as our Financial Manager.